Speech-based English sight word reading model for autistic children / Ahmad Masoud Raufi - Ahmad Masoud , Raufi (2019)
Most autistic children suffer from impairments in specific cognitive processing styles, social skills, and communication skills, which affect the academic performance of those children in school. The difficulties in communication and social skills result in the lack of motivation, attention, satisfaction, and interaction in this population and these cause them deficits in learning and especially reading the text. Hence, the purpose of this study was to develop a speech-based reading model to assist Autistic children in acquiring English reading skills. In this study, the design Science Research Method (DSRM) was used, which is a six-step method for developing and evaluating the prototype. We proposed a speech-based English sight word reading model, implemented as a Desktop-based prototype and the prototype is evaluated by 15 autistic school-aged students. The findings show that the software prototype was useful to assist Autistic children in addressing the reading deficits in this population. The targeted autistic students showed significant improvement in terms of words retention after using the CBI for ten sessions. More comprehensive speech-based models for learning reading comprehension and sentence combination are considered as future work.